The Effects of Dispositional Mindfulness and Social Support on Academic Stress Among Students in the Guidance and Counseling Program at the Faculty of Teacher Training and Education, Tadulako University - Junita A. Patabang; Dhevy Puswiartika; Ikhlas Rasido; Hasan Hasan (Journal of Educational Sciences, 2026)
College students are a group vulnerable to academic stress due to various academic demands. Academic stress can affect students’ emotional well-being, mental health, and academic performance. This study aims to examine the effects of dispositional mindfulness and social support on academic stress among students in the Guidance and Counseling Program at the Faculty of Teacher Training and Education, Tadulako University. This study employs a quantitative approach using a causal-associative method. The study population consisted of 211 students from the 2018–2022 cohorts, with a sample of 138 students selected using simple random sampling based on the Slovin formula. Data collection utilized a Likert-scale questionnaire distributed via Google Forms. Data were analyzed using descriptive and inferential statistical analysis with the aid of SPSS version 22 through classical assumption tests and multiple linear regression analysis. The results of the study indicate that dispositional mindfulness does not have a significant effect on students’ academic stress (sig = 0.051 > 0.05). Conversely, social support had a significant effect on academic stress (sig = 0.049 < 0.05). Simultaneously, dispositional mindfulness and social support had a significant effect on academic stress (F = 3.936; sig = 0.022 < 0.05). The coefficient of determination indicated that the two variables explained 4.1% of the variation in academic stress, while the remainder was influenced by other factors outside the scope of this study. The results of this study indicate that social support plays a more significant role in helping students manage academic stress than dispositional mindfulness.